Variation in biomass and soil carbon storage and sequestration rates in different agroforestry systems with climatic zones and soil types - Sabiha Yeasmin Mazumder; Jintu Kumar Bania; Gudeta Weldesemayat Sileshi; Mausam Kumar Paul; Ashesh Kumar Das; Arun Jyoti Nath (Environmental and Sustainability Indicators)
Agroforestry systems have gained substantial interest in environmental management and carbon sequestration on cropland. The expected changes in biomass and soil carbon are one of the major areas of uncertainty in greenhouse gas mitigation on croplands. Global syntheses of the carbon stocks, sequestration rates, and the uncertainties in different agroforestry systems are virtually lacking. Therefore, the objective of this study are (1) to quantify carbon storage and sequestration rate of different agroforestry systems with climatic zones and soil type, and (2) to assess the uncertainties in estimating biomass, soil carbon stocks, and sequestration rates across agroforestry systems. Using data from 129 and 121 primary studies, we estimated the global mean carbon stocks in agroforestry systems at 40.9 Mg ha−1 in biomass and 159.1 Mg ha−1 in soil up to the 100 cm depth. Approximately 3–4 times more carbon was stored in the soil than in biomass of the different agroforestry systems. We estimated carbon sequestration rates in agroforestry systems at 5.7 Mg C ha−1 year−1 in biomass and 1.4 Mg C ha−1 year−1 in the soil using data from 38 and 27 studies, respectively. Agrosilvopastoral systems stored higher mean biomass carbon and soil carbon stocks. Agrisilvicultural systems achieved higher biomass carbon sequestration rates, while agrosilvopastoral systems achieved higher soil carbon sequestration rates. Agroforestry systems in temperate climates stored higher biomass and soil carbon stocks than those in tropical climates. Agroforestry systems in subtropical climates achieved higher biomass and soil carbon sequestration rates compared to tropical and temperate regions. Agroforestry systems stored higher biomass carbon stocks on Gleysols, while those on Arenosols stored higher SOC stocks. For the first time, here we provide estimates and uncertainties associated with biomass and soil carbon stocks and sequestration rates in different agroforestry systems. These estimates may provide benchmark values against which future progress can be judged. Future progress in agroforestry can be judged by comparing field data to benchmarks: biomass carbon (40.9 Mg ha−1), soil carbon (159.1 Mg ha−1), and sequestration rates (5.7 Mg C ha−1 year−1 in biomass, 1.4 Mg C ha−1 year−1 in soil). Our findings are also expected to guide panning and decision-making regarding allocation of resource and development of evidence-based policies for environmental management using agroforestry interventions.